Citizen science: a key tool for addressing knowledge gaps in the conservation status of protected species in Tuscan Mediterranean Sea - Chiara Marescalchi; Cecilia Mancusi; Francesca Capanni; Valentina Menonna; Andrea Casadio; Gilda Ruberti; Niccolò Della Giovampaola; Francesco Bonucci; Valeria Paoletti; Massimiliano Maschio; Letizia Marsili (Estuarine, Coastal and Shelf Science, 2025)

Could persistent organic pollutants affect future generations of sea turtles by maternal transfer? First results for Caretta caretta nests along the North-Western coast of Italy - Ilaria Ceciarini; Francesca Capanni; Lorenzo Minoia; Guia Consales; Carlo Amico; Marco Alberto Luca Zuffi; Giuliana Terracciano; Cecilia Mancusi; Alessandra Neri; Enrica Franchi; Giovanni Raimondi; Alessia Prestanti; et al. (Frontiers in Marine Science, 2024)
Since 2013, loggerhead sea turtle ( Caretta caretta , Linnaeus 1758) nesting has been observed further north along the Italian coast, reaching the Tuscan coast (NW Mediterranean Sea). The four nesting events that occurred in Tuscany in the summer of 2019 spurred the scientific community to monitor these occurrences more carefully, following them from egg deposition to hatching. This provided an opportunity to collect samples for conducting multidisciplinary investigations, including the toxicological investigations of the biological material collected from the four nests. The aim of this study was to conduct an initial assessment of persistent organic pollutants in the eggs laid in Tuscany, aiming to establish a baseline on this topic for subsequent nesting events that have occurred until today. Organochlorine compounds (OCs), specifically polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane (DDT) and its metabolites, and hexachlorobenzene (HCB), were analyzed and detected in unhatched eggs, embryos, and chorio-allantoic membranes (CAMs). OCs were detected in all samples, with PCBs > DDTs ≫ HCB. A significant spatial variation in pollutant levels and profiles among sea turtle nesting locations was found. Embryos showed higher levels of contamination than egg contents regardless of the developmental stages. Depth of the laying chamber and egg mass were not significant factors in OC bioaccumulation. For the first time in the Mediterranean Sea, this study assessed the role of CAM in the transfer of contaminants to the embryo. Overall, the OC levels found were lower compared to the results from other studies conducted worldwide on loggerhead sea turtle biological material. This was the first assessment of nest biological material for the North-Western coast of Italy.

Monk seals (Monachus monachus) in the Mediterranean Sea: The threat of organochlorine contaminants and polycyclic aromatic hydrocarbons - Francesca Capanni; Alexandros A. Karamanlidis; Panagiotis Dendrinos; Annalisa Zaccaroni; Costanza Formigaro; Antonella D'Agostino; Letizia Marsili (Science of The Total Environment, 2024)

Gene Expression Profiling of Trematomus bernacchii in Response to Thermal and Stabling Stress - Samuele Greco; Anastasia Serena Gaetano; Gael Furlanis; Francesca Capanni; Chiara Manfrin; Piero Giulio Giulianini; Gianfranco Santovito; Paolo Edomi; Alberto Pallavicini; Marco Gerdol (Fishes, 2022)
The Antarctic continent is one of the most pristine environments on planet Earth, yet one of the most fragile and susceptible to the effects of the ongoing climate change. The overwhelming majority of the components of Antarctic marine trophic chain are stenotherm organisms, highly adapted to the extreme, but extremely stable, freezing temperatures of the Antarctic ocean, which have not changed significantly during the past fifteen million years. Notothenioid fishes are the most abundant representatives of ichthyofauna at these latitudes, being ubiquitously found in coastal areas across the entire continent. While different Antarctic fish species have been previously subjected to studies aimed at defining their range of thermal tolerance, or at studying the response to acute thermal stress, just a handful of authors have investigated the effects of the exposure to a moderate increase of temperature, falling within the expected forecasts for the next few decades in some areas of the Antarctica. Here, the emerald rockcod Trematomus bernacchii was used as a model species to investigate the effects of a 20-day long exposure to a +1.5 °C increase in the brain, gills and skeletal muscle, using a RNA-sequencing approach. In parallel, the experimental design also allowed for assessing the impact of stabling (including acclimation, the handling of fishes and their confinement in tanks during the experimental phase) on gene expression profiling. The results of this study clearly identified the brain as the most susceptible tissue to heat stress, with evidence of a time-dependent response dominated by an alteration of immune response, protein synthesis and folding, and energy metabolism-related genes. While the gills displayed smaller but still significant alterations, the skeletal muscle was completely unaffected by the experimental conditions. The stabling conditions also had an important impact on gene expression profiles in the brain, suggesting the presence of significant alterations of the fish nervous system, possibly due to the confinement to tanks with limited water volume and of the restricted possibility of movement. Besides providing novel insights in the molecular mechanisms underlying thermal stress in notothenioids, these findings suggest that more attention should be dedicated to an improved design of the experiments carried out on Antarctic organism, due to their extreme susceptibility to the slightest environmental alterations.